The role of hydrological factors in the die-back of the European spruce in the territory of the Southeast Carpathians - Kravchynskyi, Ruslan; Khilchevskyi, Valentyn K.; Korchemlyuk, Marta; Zabokrytska, Myroslava R.; Stefurak, Olga; Belmega, Ivan (V. N. Karazin Kharkiv National University, 2024)
The article is dedicated to studying the processes of European spruce stand dieback, a phenomenon that is currently relevant not only in Ukraine but also in most European countries, including the Czech Republic, Slovakia, Germany, Austria, and Poland. The focus is on an in-depth investigation of the relationships between one of the abiotic components – the hydrological factor – and the locations where European spruce dieback occurs on the southeastern slopes of the Carpathians. Geographically, the research area is outlined by the boundaries of the first and one of the largest nature parks in Ukraine, the Carpathian National Nature Park (NNP). Purpose. The aim of the study is to identify the relationships between the processes of European spruce dieback and dynamic and quasi-static (relatively constant) hydrological descriptors in the southeastern Carpathians. Methods. The informational basis for the study includes the results of forest pathology research conducted by specialists of the Carpathian NNP in 2022, along with long-term hydrometeorological observation data from the Carpathian Flood Monitoring Station Network (Ukrainian Hydrometeorological Center of the State Emergency Service of Ukraine). The study also utilized various remote sensing, field, dendrochronological, laboratory, analytical, comparative, cartographic, mathematical, and instrumental methods. Research results. The research established that zones of spruce stand dieback are linked to stream source systems, associated with "meanders" in river channels, and are localized near water springs, particularly those with unique chemical water composition. These features may serve as indirect indicators of connections with regional and local tectonic disturbances. The study found a significant relationship between the annual growth of European spruce trunks and the average annual water discharge of the Prut River (r = 0.6) and the annual precipitation in the area (r = 0.68). In areas where spruce dieback is active, a distinctive evaporation mist formation regime and soil moisture patterns were observed. Temporally, the timing of spruce dieback appears to be connected to abrupt changes in annual water discharge and precipitation levels, likely indicating the impact of "water stress" on the biotic resilience of Picea abies [L.] Karst. Conclusions. The results of this research can contribute to local, regional, or global models for spatiotemporal forecasting of spruce stand dieback processes, not only in the Carpathian region but also in other areas where this issue is relevant. The conclusions and recommendations presented in the article are important for the development of the local tourism and recreation sector, for planning forestry management activities, and for scientific and educational purposes (including conducting scientific excursions and field practices for students in natural sciences, among others).
Keywords: European spruce (Picea abies [L.] Karst); dead trees; southeastern Carpathians; hydrography; springs; climate change; evaporation; water balance; annual average streamflow